ANALYSIS OF VARIABLES AFFECTING LAND VALUE IN EARTHQUAKE-PRONE AREAS, LEMBANG FAULT ZONE (CASE STUDY: BANDUNG CITY, WEST JAVA PROVINCE) - Saddam Maladi, Muhammad
Indonesia's inclusive wealth grew by 39% from 1990 to 2014 with the implication that the value of increasing the quality of life increases as the population's need for space increases. The city of Bandung as an area with a high risk of earthquake-disaster – its proximity to the Lembang Fault contributes to a high potential for disaster – is a densely populated area. However, the earthquake-disaster aspect is not one of the determining factors for the value of land according to the competent authority regarding land valuation and issuance of the Land Value Zone Map (ZNT). Therefore, it is necessary to analyze the variables that affect the value of land in Bandung City by considering the earthquake-disaster aspect. This study attempts to model a Land Value Zone Map based on four factors, namely Social Factors, Economic Factors, Government Factors, and Physical Factors. Modeling the value of land in Bandung City as an earthquake-prone area uses a sample through a questionnaire aimed at experts in cadastral, land and tax assessment. The results of the questionnaire resulted in a weighting variable determining land value using the Analytic Hierarchy Process (AHP) method to be processed using spatial analysis using the Spatial Multi-Criteria Evaluation (SMCE) framework. This research produced two land value estimation models with Tangible and Intangible Criteria and with Physical and Non-Physical Criteria. Based on the results obtained, the model that considers the earthquakedisaster aspect has a lower land value than the actual field conditions – the earthquakedisaster aspect does not have a significant effect on the market value of land.